Presence of Yellow 6, an Artificial Colour Additive in Orange Juice - Sultana, Abida; Haque, Mohammad S; Shoeb, Mohammad; Islam, M Saiful; Mamun, M Iqbal R; Nahar, Nilufar (Journal of the Bangladesh Chemical Society, 2012)
Soft drinks and orange juices are very popular all over the world including Bangladesh. Yellow 6 (Disodium 6-hydroxy-5-(4-sulfophenyl) azo-2-naphthalenesulfonate) was used in food and drinks as color additives earlier but due to its adverse effects on human health, yellow 6 has been banned in many countries. However, this harmful color additive yellow 6 is being used in commercial orange drinks in Bangladesh. Ten commercial brand yellow colored soft drinks and juices were analyzed to find out the presence of yellow 6. Juice prepared from fresh fruits was used as control. The UV-visible absorption maxima of yellow 6 is 429 nm. The amount of yellow 6 in commercial brands and fresh orange juices was determined by UV-visible spectrophotometer. Out of ten samples, seven juice samples were found to contain yellow 6 in the range of 0.83-1.66 mg/mL. Fresh juice did not show any absorption at 429 nm. This is an easy and cost effective method to assess the presence of yellow 6 in orange juice and the method can be used for other food stuffs. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11778 Journal of Bangladesh Chemical Society, Vol. 25(1), 80-86, 2012